Sosialisasi dan Edukasi Pembuatan Slide Presentasi Menggunakan Aplikasi Canva bagi Siswa-Siswi di SMPN 4 Tewah, Kabupaten Gunung Mas - Apriyanti, Mauliya; Pereiz, Zimon; C, Chuchita; Oksal, Efriyana; Telaumbanua, Mesra Ratna Sari; Sabatini, Felly; J, Julia; Solla, Angelia; Prasetyo, Debby Catur; Hutabalian, Gracyela; A, Anjelika; H, Heja; Florensia, Ornella Arnia; Devianti, Gusnia; Prayoga, Andika; Tundan, Arisumi Ir L; Dandy, Jonathan; A, Abdullah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The socialization and educational program on creating presentations using the Canva application was conducted at SMPN 4 Tewah, Gunung Mas Regency, Central Kalimantan, as an effort to improve students’ digital literacy and communication skills in the technological era. Canva was chosen because it is an online-based design application that is accessible, user-friendly, and offers a wide variety of attractive templates to support students’ creativity in preparing presentation materials. The main objectives of this program were to provide a basic understanding of Canva usage, train students in designing effective presentation slides, and foster their confidence in delivering ideas. The implementation method included socialization, hands-on training, and practice in creating presentations based on learning themes. The results indicated that most students were able to understand Canva’s basic functions, utilize its features, and produce more engaging and communicative presentations compared to before. Moreover, this activity increased students’ enthusiasm and motivation to learn, particularly in using digital technology to support their academic progress. Therefore, this socialization and educational program made a positive contribution to enhancing the digital competence of SMPN 4 Tewah students, while also supporting the achievement of educational goals in the digital era.